1990
DOI: 10.1073/pnas.87.19.7727
|View full text |Cite
|
Sign up to set email alerts
|

Evidence for susceptibility of intrathymic T-cell precursors and their progeny carrying T-cell antigen receptor phenotypes TCR alpha beta + and TCR gamma delta + to human immunodeficiency virus infection: a mechanism for CD4+ (T4) lymphocyte depletion.

Abstract: Individuals infected by the human immunodeficiency virus type 1 (IV-i) demonstrate progressive de-

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
66
0

Year Published

1993
1993
2010
2010

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 113 publications
(67 citation statements)
references
References 33 publications
1
66
0
Order By: Relevance
“…Others have reported infection of thymic TCR␥␦ clones in vitro (59,60), suggesting the potential for direct infection by HIV-1 in vivo. For the most part, TCR␥␦ cells in the periphery do not express CD4, and thus the only point at which TCR␥␦ ϩ cells are naturally susceptible to HIV-1 infection is during development in the thymus when CD4 is expressed (23).…”
Section: Discussionmentioning
confidence: 99%
“…Others have reported infection of thymic TCR␥␦ clones in vitro (59,60), suggesting the potential for direct infection by HIV-1 in vivo. For the most part, TCR␥␦ cells in the periphery do not express CD4, and thus the only point at which TCR␥␦ ϩ cells are naturally susceptible to HIV-1 infection is during development in the thymus when CD4 is expressed (23).…”
Section: Discussionmentioning
confidence: 99%
“…In vitro studies have shown that HIV-1 can infect thymocytes from uninfected subjects, and in vivo studies in the SCID-hu chimera model have shown that immature thymocytes are infected by HIV-1 and implicate HIV as the direct (3)(4)(5) and indirect (6, 7) cause of thymocyte death. Although information on infection of thymocytes in vivo is limited, a report analyzing thymic tissue obtained from an infant with perinatal HIV-1 infection demonstrated infection in immature thymocytes (1).…”
mentioning
confidence: 99%
“…In addition there were clusters of HIV-infected CD34 + stem cells identified in the subcortical regions of these thymuses. HIV also disrupts thymopoiesis by direct infection of thymocytes [12][13][14][15][16][17][18][19][20][21][22][23][24][25][26]. Utilizing the SCID-hu thy/liv model that was then challenged with HIV-1, investigators demonstrated that thymopoiesis was impaired by direct infection of thymocytes.…”
Section: Discussionmentioning
confidence: 99%
“…Antibody crossreactive to core p17 and p24 HIV antigens and thymic epithelial proteins has been observed in the HIV-infected thymus, suggesting an autoimmune component to HIV damage. In addition are the observations that human fetal thymus/liver organs transplanted into severe-combined immunodeficient (SCID) mice (SCID-hu thy/liv) in in vitro human models of thymopoiesis demonstrate that both HIVinfected thymocytes and T cells induce thymic epithelial cell injury [13][14][15][16][17][18][19][20][21][22][23]. Abnormal thymic epithelia synthetic function has been demonstrated by decreased synthesis of thymic hormones, such as thymosin-α1 and thymosin-β4 [14].…”
Section: Discussionmentioning
confidence: 99%